Kristuskarakteristik og eksempelfortælling: Fristelsen i ørkenen (Matt 4,1-11 og Luk 4,1-13) i nyere danske børnebibler - Bylund, Louise Heldgaard (Dansk Teologisk Tidsskrift, 2019)
During its history of interpretation and reception, the temptation story in Matthew 4:1–11 and Luke 4:1–13 has been interpreted with emphasis on either its Christological or its paraenetical dimension. The article investigates how contemporary Danish children’s bibles retell the story with accent on the paraenetic elements. The children’s bibles reframe the story according to the genre of the morality tale. With literary devices such as focalization, metalepsis, shared interest and reader involvement strategies, the children’s bibles portray Jesus as a positive moral example for readers to emulate. This implies a view of the intended reader as a competent child who is capable of understanding and identifying with the text and overcome the devil’s temptations.